Partial Depletion of Peripheral M1 Macrophages Reverses Motor Deficits in MPTP-Treated Mouse by Suppressing Neuroinflammation and Dopaminergic Neurodegeneration - Yan, Aijuan; Zhang, Yu; Lin, Jingya; Song, Lu; Wang, Xijin; Liu, Zhenguo (Frontiers in Aging Neuroscience, 2018)
Background: Neuroinflammation plays an important role in the pathogenesis of Parkinson's disease (PD). Inflammatory cytokines in the peripheral immune system can induce neuroinflammation in central nervous system (CNS). Whether the peripheral immune system is involved in PD is unclear. The present study investigated the contribution of the peripheral immune system to the neuronal loss in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine(MPTP) model of PD. Methods: MPTP was intraperitoneally injected into mice to generate a PD model. Mice received clodronate liposomes every 3 days to deplete peripheral macrophages. The percentages of macrophages were measured by flow cytometry at 1,3,7 days after MPTP injection. Neurobehavioral parameters, protein expression, inflammatory cytokines release, and microglia activation were measured by the open field test, western blotting, quantitative polymerase chain reaction (qPCR), and immunofluorescence staining, respectively at 7 days after MPTP injection. Results: Our study revealed that intraperitoneal injection of MPTP could increase peripheral M1 macrophages levels. It also can induce T cells infiltration and cytokine release. Depletion of M1 macrophages by clodronate liposomes suppressed these inflammatory effects and blunted the loss of TH+ nigral neurons and functional impairments caused by MPTP. Conclusion: Our results indicated the critical role of M1 macrophages in the pathogenesis of PD and proposed inhibition of M1 macrophages as a promising therapeutic approach for neurodegeneration.